Positive solutions for a coupled system of nonlinear second order eigenvalue problems (2015)
In this work, we consider a system of coupled nonlinear second order eigenvalue problems. Under suitable conditions, existence of positive solutions are established, for determined eigenvalues, by the use of abstract fixed-point.